Gold-silica nanocoating of DNA origami - Djuphammar, August (My University, 2022)
Finding new ways to empirically determine the 3D structure of biomolecules could greatly increase our knowledge of their function or toxicity. A long-standing issue is that biomolecules are sensitive and therefore difficult to analyze without disrupting their structure, and thereby invalidating the measurement. A promising imaging technique is atom probe tomography, which has high lateral and axial resolution, while obtaining chemical composition through mass spectrometry, yet the sensitivity issue of biomolecules remains. This Master’s thesis aims to compose an atom probe tomography sample fabrication route for biomolecules, by initially stabilizing the 3D structure with nanoshells. DNA origami was folded to a distinguishable and known structure to evaluate if the nanoshell coating process affects the structure or if it is preserved. A modified St¨ober process was used to form a thin silica shell around the DNA origami. This was done at mild conditions to preserve the native structure, and followed by a gold coating step, resulting in multi-layered core-shell particles. Scanning electron microscopy images and transmission electron microscopy images of the particles revealed features corresponding to the known DNA structure suggesting successful nanoshell synthesis and 3D structure preservation. What remains before atom probe tomographic analysis is possible is to form needle shaped samples with the particles at the apex, and two such paths are presented and explained as future work. The protocol could then be applied to other biomolecules with unknown structures to obtain both the chemical composition and the shape.
Keywords: DNA origami; Nanoshells; Nanoparticles; Atom probe tomography; 3D imaging; Nanobiotechnology